2014
DOI: 10.2147/opth.s69883
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for medically refractory myasthenic blepharoptosis

Abstract: PurposeCurrently, only a few reports have recommended surgery as a suitable treatment for blepharoptosis associated with myasthenia gravis. The present study aims to introduce our surgical criteria, surgical options, outcomes, and precautions for medically refractory myasthenic blepharoptosis.Patients and methodsEight patients who failed to respond to at least 2 years of medical treatment and who underwent blepharoptosis surgery, from January 2008 to December 2011, were enrolled in this study. Medical records,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Ptosis can temporarily improve with edrophonium/pyridostigmine testing (acetylcholinesterase inhibitor) or ice pack testing (slowed enzymatic activity of acetylcholinesterase). Surgical ptosis correction requires meticulous selection of candidates that have experienced medical therapy failure or have been stable on medical therapy for 3-4 years [43] . With external levator advancement, 80%-90% of patients can achieve increased lid height [44,45] .…”
Section: Neurogenic Ptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Ptosis can temporarily improve with edrophonium/pyridostigmine testing (acetylcholinesterase inhibitor) or ice pack testing (slowed enzymatic activity of acetylcholinesterase). Surgical ptosis correction requires meticulous selection of candidates that have experienced medical therapy failure or have been stable on medical therapy for 3-4 years [43] . With external levator advancement, 80%-90% of patients can achieve increased lid height [44,45] .…”
Section: Neurogenic Ptosismentioning
confidence: 99%
“…Thyroid eye disease can uncommonly present with ptosis and must be managed with corticosteroids and/or immunomodulatory therapy to ensure 6-9 months of stability before eyelid surgery can be considered [85,86] . Given the significant fluctuation of levator function in MG, cholinesterase inhibitors and/or corticosteroids should ideally be titrated to ensure stabilization for 3-4 years prior to surgical correction [43] . While not true ptosis, neuromyotonia of the levator palpebrae superioris has been documented to cause pseudoptosis of the contralateral eye via Hering's law of equal innervation.…”
Section: Pharmacologicmentioning
confidence: 99%
“…Supportive measures as crutch glasses for severe ptosis and prisms in patients with diplopia are helpful in treatmentresistant OMG. Ptosis surgical correction is effective and well-tolerated when exposure keratitis is avoided (90,111); the possibility of diplopia worsening should be discussed beforehand. Topical naphazoline, a mainly α2-agonist, was found to be effective in relieving mild to moderate ptosis (112).…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Although we have performed both lid elevation and ocular realignment surgery on a few cases with treatment‐resistant OP‐MG, the results are similar to other published cohorts, and a few conclusions can be drawn. A Japanese series found that seven of eight patients who underwent lid‐elevation procedures for treatment‐resistant myasthenic ptosis, present for at least 2 years and with minimal circadian changes, were satisfied with the outcome . The Mayo clinic described nine patients who underwent surgery for treatment‐refractory ptosis after trying MG therapies for at least 12 months; half of their cases required additional procedures owing to undercorrection of ptosis, but this is preferable to overcorrection and secondary‐exposure keratitis …”
Section: Managing the Disability Of Op‐mgmentioning
confidence: 99%